2010
DOI: 10.3386/w15935
|View full text |Cite
|
Sign up to set email alerts
|

Can Pollution Tax Rebates Protect Low-Income Families? The Effects of Relative Wage Rates

Abstract: Pollution taxes are believed to burden low-income households that spend a greater than average share of income on pollution-intensive goods. Some propose to offset that effect by returning revenue to low-income workers via reduced labor tax. We build analytical general equilibrium models with both skilled and unskilled labor, and we solve for expressions that show the change in the real net wage of each group. A decomposition shows the effect of the tax rebate, the effect on the uses side of income (higher pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The rest of the term consists of the net gains or losses from redistributing the fiscal revenue for all groups, including appropriation costs, as specified in Eqs. (25) and (26).…”
Section: Welfare Comparisonmentioning
confidence: 98%
See 1 more Smart Citation
“…The rest of the term consists of the net gains or losses from redistributing the fiscal revenue for all groups, including appropriation costs, as specified in Eqs. (25) and (26).…”
Section: Welfare Comparisonmentioning
confidence: 98%
“…Many studies have shown the distributional impacts of alternative uses of revenues [8,12,17,23,25,27,47,56]. In particular, many studies have found that simple lump-sum transfers tend to perform worse than alternatives, such as reducing distortionary taxation, increasing tax credits, and financing government investments.…”
Section: Creation Of the Contestable Rentmentioning
confidence: 99%
“…Less studied and largely absent from public debate than effects through consumer prices are the distributional effects from carbon pricing that can also arise on the income side of households' accounts. Fullerton and Monti (2010) emphasize the potential importance of changes in relative wage rates across different segments of the labor market-and suggests 43 IEA (2010) estimates global subsidies across all fossil fuels at approximately $550 billion per year: about $300 billion for oil, $200 billion for gas, and $50 billion for coal; about$100 billion is subsidized electricity generation inputs, and the rest direct use subsidies. See also Joint Group Report (2010).…”
Section: Equity Aspectsmentioning
confidence: 99%
“…Distributional concerns also arise from shifting returns to factors of production. Fullerton and Monti (2010), for example, emphasises the potential importance of changes in relative wage rates across different segments of the labor marketsuggesting that a higher propensity for low skill workers to be employed in polluting sectors (more affected by the tax) may increase distributional concerns regarding a carbon tax in the US.…”
Section: Pricing Carbon and Strengthening Public Financesmentioning
confidence: 99%